Native Americans and the Christian Right The Gendered Politics of Unlikely Alliances - Smith, Andrea (Duke University Press, 2008)
In Native Americans and the Christian Right, Andrea Smith advances social movement theory beyond simplistic understandings of social-justice activism as either right-wing or left-wing and urges a more open-minded approach to the role of religion in social movements. In examining the interplay of biblical scripture, gender, and nationalism in Christian Right and Native American activism, Smith rethinks the nature of political strategy and alliance-building for progressive purposes, highlighting the potential of unlikely alliances, termed "cowboys and Indians coalitions" by one of her Native activist interviewees. She also complicates ideas about identity, resistance, accommodation, and acquiescence in relation to social-justice activism. Smith draws on archival research, interviews, and her own participation in Native struggles and Christian Right conferences and events.